If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5=p/4-2
We move all terms to the left:
5-(p/4-2)=0
We get rid of parentheses
-p/4+2+5=0
We multiply all the terms by the denominator
-p+2*4+5*4=0
We add all the numbers together, and all the variables
-1p+28=0
We move all terms containing p to the left, all other terms to the right
-p=-28
p=-28/-1
p=+28
| 6(x+2)=3x+18 | | -½(24-6h)=3(h-4) | | -74=-(1-x)+6(8x-4) | | 14+2=—4k | | 8x-6x-25=-35* | | 2x+4+7x=32 | | 3(4x-7)=-9 | | 32+6x=14x-4 | | -7x-15=3x+25 | | 10j+10j=100 | | x/4+7=11* | | 26=7(6x-2)+2(x-2) | | 24=-12t | | 32+6x=(7x-2)2 | | 6h-5h=11 | | 7(x+1)=6x+12 | | -5x+4=-80-8x | | 46+3x+62=93+47+4x | | 13x-13=2x+13 | | 2x+25=5x22 | | –6+8n=5n | | 3+x=63 | | s+612;s=7 | | -15m=4m+5 | | 2(-6d+5)=-4d+2* | | 12=-12t | | 5x+10=-5+40 | | 6h-5=11 | | P(x)=x4-12x2-64;x=4 | | 50=-7x | | 4=2p−2 | | 20g+-3g=34 |